Myeloid-derived suppressor cells exhibit distinct characteristics in bone marrow and blood of individuals with diffuse large B-cell lymphoma - Paris Efstratiou; Athina Damianaki; Aglaia Kavidopoulou; Polymnia Ioannidou; Effrosyni Markaki; Ioannis Moysis Skianis; Electra Tsagliotis; Vasilia Kaliafentaki; Angelos Mattheakakis; Maria Ximeri; Eleftherios Manouras; Matthieu Lavigne; et al. (Frontiers in Medicine)
Antitumor immune surveillance is the key feature of tumour progression and response to treatment in various malignancies, such as lymphomas. Myeloid derived suppressor cells (MDSCs) are bone marrow (BM)-derived cells with potent suppressive properties, implicated in T cell inhibition and tumour dissemination. In Diffuse Large B-cell Lymphoma (DLBCL), circulating MDSCs constitute the immunosuppressive tumor microenvironment, while the contribution of BM MDSCs in disease pathogenesis remains elusive. In the present study we aimed to evaluate both the frequencies as well as the molecular signatures of MDSCs in blood and BM from newly diagnosed DLBCL patients prior to treatment initiation and from age matched healthy donors. Circulating levels of total, monocytic (M-) and polymorphonuclear (PMN-) MDSCs were found increased in DLBCL compared to healthy control, while in DLBCL patients the BM MDSCs were significantly increased compared to blood. Transcriptomic analysis revealed significantly different molecular fingerprints to characterize circulating and BM M-MDSCs, implying that MDSCs exhibit their function with distinct mechanisms depending on the anatomical compartment. Despite that MDSC frequencies did not demonstrate any significant correlation with disease characteristics and outcome, our findings propose that gene expression profiling should be evaluated for their potential prognostic impact. Overall, the findings presented here, provide new insights in the immunosuppressive networks that operate in DLBCL and importantly propose new molecular mechanisms expressed by BM MDSCs which may be explored therapeutically.